Perceptions of mental health professionals towards artificial intelligence in mental healthcare: a cross-sectional study - Sharif, Loujain; Almabadi, Reem; Alahmari, Alhanouf; Alqurashi, Fai; Alsahafi, Fidaa; Qusti, Shahad; Akash, Walaa; Mahsoon, Alaa; Poudel, Dev Bandhu; Sharif, Khalid; Wright, Rebecca (Frontiers in Psychiatry, 2025)
BackgroundArtificial intelligence (AI) holds significant potential for enhancing mental health care, but uptake is limited, potentially impacted by demographic factors of healthcare professionals. Further, while AI use in Saudi Arabia is progressive, there is minimal exploration of its role and impact within mental health services.ObjectiveThis study presents a unique exploration of psychiatric professional’s perceptions of AI in mental health care in Jeddah, Saudi Arabia.MethodsA cross-sectional online survey was conducted with a sample of mental health professionals from two governmental mental health hospitals in Jeddah, Saudi Arabia. The study tool was made up of two sections, the first consisting of sociodemographic questions and the second was the Shinners Artificial Intelligence Perception (SHAIP) questionnaire assessing the perceptions towards AI in mental healthcare, with data analyzed using IBM SPSS Statistical software.ResultsA total of 251 mental health professionals, mostly females (56.6%), aged 31-40 (50%), married (45%), and nurses (55.4%). Only 24.3% used AI in practice, though 85.7% were aware of AI. Participants positively rated AI’s impact (mean item range: 3.48-3.75) and felt unprepared for role-specific AI (mean 2.78). Nurses and those aware of AI had higher AI impact perceptions (p<0.0001) Specialty and AI awareness affected AI preparedness (p=0.001, p=0.029).DiscussionThe study provides insights into mental health professionals ‘ views on AI in mental healthcare, emphasizing the need for targeted education to improve AI literacy and preparedness among Saudi healthcare professionals. It highlights the importance of ethical AI implementation to enhance patient care and advance psychiatric practice in the region.